Osh risk management of tank sinking procedure using bow tie analysis on the construction of a shell gasoline station in Surabaya - Wijaya, Oktomi; Sugiyana, Laely Ufiz Tsani (Periodicals of Occupational Safety and Health, 2022)
Introduction: The rate of work accidents in the construction sector is still high. Such a situation has led to the need for risk management in the area of Occupational Safety and Health (OSH). This study is aimed at finding the OSH risk management of the tank sinking procedure using Bow Tie Analysis method in the construction of a Shell Gasoline Station in Surabaya. Methods: This is a qualitative descriptive study with case study design. The subjects of the study were the employees of PT Usaha Jaya Engineering who worked on the Tank Sinking procedure in the construction of a Shell Gasoline Station in Surabaya with the minimum service period of 2 years and with a total number of 7 people.  Data collection was executed using primary data derived from interviews and field observation as well as secondary data in the forms of supporting documents from the company. Results: As many as 9 hazards were found in the tank sinking procedure in the construction of a Shell Gasoline Station in Surabaya. These hazards were caused by 5 factors, i.e., human, machine/equipment, method, material, and environment. The possible consequence of such hazards is that the employees may experience light to serious injuries and even fatality. Prevention and mitigation measures might be implemented in 4 hierarchical steps of risk management, i.e., substitution, technical management, administrative management, and personal protective equipment (PPE). This study found 6 escalation factors and the barrier of escalation factor in the tank sinking process. Conclusion: The tank sinking procedure in the construction of a Shell Gas Station in Surabaya was a job with risks of work accident. Prevention and mitigation measures derived from the Bow Tie analysis might be implemented to prevent work accidents from occurring.